PENYULUHAN PENGELOLAAN LIMBAH B3 PADA KEGIATAN TAMBAK UDANG INTENSIF DI DESA LABUHAN SANGORO KECAMATAN MARONGE KABUPATEN SUMBAWA - Astriana, Baiq Hilda; Putra, Aryan Perdana; Adiansyah, Joni Syafaat (Universitas Mataram, 2024)
Sumbawa Regency is a district with an area of 3,619.50 Ha is used for shrimp farming activities. This area continues to increase along with increasing shrimp production. In shrimp farming operations, supporting facilities and infrastructure used can produce Hazardous and Toxic waste (B3) resulting from maintenance of generator engines, water wheel gear boxes, and others. Changes to government and ministerial regulations regarding B3 waste management need to be conveyed to fish farming business actors so that they can comply with the provisions for B3 waste management. Therefore, this service aims to educate shrimp farming managers regarding the management of B3 waste according to the latest regulations including packaging and storage methods for B3 Waste as well as identifying the B3 Waste produced. The method used in this activity is to provide knowledge to the managers of PT Maja, an intensive shrimp farming regarding identification of types of B3 Waste, packaging of B3 Waste and storage of Hazardous and Toxic Waste produced during shrimp farming operational activities. Based on the results of this activity, it was concluded that there was an increase in the understanding of farming managers regarding the management of B3 waste both in terms of packaging and storage based on Regulation of the Minister of State for the Environment Number 6 of 2021 concerning Procedures and Requirements for Management of B3 Waste. Apart from that, based on the identification of B3 waste types, it was identified that 469.3 liters of used oil, 11 pcs of used oil filters, and 4 units of oil containers were produced every year. Based on the results of this activity, it is known that the participants' insight into B3 waste management has increased after participating in this activity.